Microseismic positioning of an isolated working face under complex geological conditions and its engineering application - Long, Zhao (Frontiers in Earth Science, 2023)
In view of the inability to accurately locate vibrations in isolated workings under complex geological conditions, an adaptive rotational categorization method, a downhill comparison method based on time-frequency analysis (TFA-DC method), a variable-step acceleration search method, and a dual-phase seismic source location method (TD-DL method) are proposed. A set of integrated software with features of “visualization”, “interactive” and “one-click” was developed for microseismic data processing. Results show that compared with the improved STA/LTA method, the recognition accuracy of the island working face microseismic signal by the adaptive wheel classification method is increased by 4.8%. Compared with the improved STA/LTA method, the TFA-DC method has the advantage that it can simultaneously pick up the exact p wave and the peak S wave, and the failure ratio is 0. Compared with simulated annealing algorithm and genetic algorithm, stepwise accelerated search method has better results. The standard deviation of objective function value, location error and wave velocity error are all 0. Method improves the positioning of the TD - DL detector coordinates, dual phase and coherence of known information, such as the positioning result positioning error is only the p wave and S wave ChanZhen phase positioning method of 9.5% and 14.5%, to a certain extent offset the p wave and S wave ChanZhen phase calculation of the positioning error, so as to improve the effect of source localization precision of the inversion.